ChemInform Abstract: Recent Applications of Ring‐Rearrangement Metathesis in Organic Synthesis. Issue 12 (March 2016) - Kotha, Sambasivarao; Meshram, Milind; Khedkar, Priti; Banerjee, Shaibal; Deodhar, Deepak
Abstract: Review: [71 refs.